Berczeli Anzelm Károlyhoz - Kozocsa Sándor (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1932)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek